Concrete Strength Evaluation Using Manufactured Sustainable Binary-Cement (SI): New Approach Case Study - Al-Baghdadi, Hayder A.; Abbas, Zena K.; Abbood, Ahlam A.; Mahmood, Raghad S. (Salehan Institute of Higher Education, 2025)
The production of sustainable binary cement represents an innovative approach in blended cement manufacturing, aligning with environmental objectives by reducing the reliance on ordinary Portland cement and supporting waste disposal efforts. This study explores the partial replacement of cement with high-fineness powders derived from crushed and ground clay brick (CB) and window glass (WG) waste materials, used at replacement levels of 5%, 10%, and 15%. These materials were processed using a storming machine to achieve the desired particle fineness and incorporated into the cement to create what is referred to as sustainable cement (SI). The resulting binary cement formulations were evaluated and found to comply with the setting time, compressive strength, and chemical specifications outlined in ASTM C595. To further assess their performance, the sustainable cements were tested in concrete mixtures designed for three compressive strength levels—2000 psi, 5000 psi, and 7000 psi—in accordance with ACI 211.1, representing low, medium, and high strength applications, respectively. Two groups of mix designs were developed: MSI-B5, MSI-B10, MSI-B15 (with CB powder replacing 5%, 10%, and 15% of cement), and MSI-G5, MSI-G10, MSI-G15 (with WG powder at the same replacement levels). The results demonstrated notable improvements in compressive strength at the low-strength level. Specifically, cumulative strength increases were recorded as 15.8%, 21.9%, and 13% for MSI-B5, MSI-B10, and MSI-B15, respectively, and 12.2%, 15.5%, and 8.1% for MSI-G5, MSI-G10, and MSI-G15, respectively, when compared to the reference mix. In addition to compressive strength, enhancements in flexural and splitting tensile strengths were also observed, exhibiting a strong correlation with compressive performance. These findings support the potential of sustainable binary cement—utilizing CB and WG powders—as a viable and environmentally friendly alternative in concrete production across varying strength classes.